RFID - based Interactive Log Bag for Poor Memory Prevention - Mohd Yazed, Muhammad Syukri; Mahmud, Farhanahani (International Journal of Integrated Engineering, 2016)
People are sometimes forgotten about what they should do or what they need to bring. Poor memory problem that happened in people less than 40 years old is due to their attitudes that like to ignore things and carelessness. An Interactive Log Bag has been developed using Arduino Mega 2560 with Radio Frequency Identification (RFID) system to help people overcome the poor memory problem of bringing or keeping essential items in a bag before travelling or going to work. The bag will react to the user RFID-tagged objects for the items logging purpose. The logging items will be saved in the SD card and can be shown in Messenger Bag Android Application. An alert system by using strip RGB Light Emitting Diode (LED) will remind the users of the forgotten items. In addition, the list of items that are left behind or carried in the bag can be checked through an android application. This project will give an opportunity to the users to have a better life by overcoming one of the daily routine problems pertaining to the forgetfulness problem.